Green engineered nano MgO and ZnO doped with Sm3+: Synthesis and a comparison study on their characterization, PC activity and electrochemical properties. (April 2019) - Kumar, M.R. Anil; Nagaswarupa, H.P.; Ravikumar, C.R.; Prashantha, S.C.; Nagabhushana, H.; Bhatt, Aarti S.
Abstract: Structural, photocatalytic, photoluminescence and electrochemical activities of rare earth (RE) metal ions (Samarium (Sm 3+ )) doped Magnesium oxide (MgO) and Zinc oxide (ZnO) nanoparticles (NPs) prepared by using Cicer artinum powder as a fuel via green solution combustion method were discussed in detail. The synthesized NPs were found to have an average crystal size of around 25 nm as established by powder X-ray diffraction (PXRD). The semiconductor behavior has been confirmed by the study of energy band gap via diffuse reflectance spectroscopy (DRS). The conductivity of the samples was studied by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). It was observed that on 378 and 398 nm excitation of both the samples, it emits yellow and white radiation resonating with the ideal white light. The Rare Earth (RE) doped NPs have been applied as a novel photocatalyst for removal of rodhamin-B (rh-B) and malachite green (MG) dyes. The release of OH radicals played a crucial role in dye degradation; its extent depending on the chemical structure and photocatalyst dosage. The photocatalytic activity (PCA) was found to be maximum for MgO:Sm 3+ (0.1 mol %) under UV light and ZnO:Sm 3+ (1 mol %) under sunlight. Graphical abstract: Graphical representation of Characterization of MgO and ZnO. Image 1 Highlights: Eco friendly green combustion route is used for the synthesis of ZNPs and MNPs doped with Sm 3+ . MNPs show emission in the red region; it was quite useful for WLEDs. ZNPs show emission in the white region; it was quite useful for WLEDs. ZNPs exhibited superior photocatalytic activity compared with MNPs under UV and sunlight.